Awareness towards green hotel among Umk students - Subramaniam, Karthiga; Abd Karim, Khairulnur Najwa; Lim, Xiu Ping; Abdul Rahim, Noor Muntazzira (2015)
The purpose of this study was to identify the relationship between environmental issues, campaign and level of knowledge to create awareness towards green hotel among UMK students. 350 survey questionnaires were used to collect the data. The entire 350 survey questionnaires are collected from the respondents studying in the UMK Pengkalan Chepa. Based on the Correlation Coefficient result, it show that level of knowledge have a moderate relationship with awareness towards green hotel with a coefficient of 0.531. However, campaign has a weak relationship with awareness towards green hotel and with a coefficient of 0.431. Environmental issues have a very weak relationship with awareness towards green hotel with a coefficient of 0.281. The environmental issues, campaign and level of knowledge indicate that correlation coefficient is highly significant at the level of 0.000. This shows that, the awareness towards green hotel among UMK students is related to the environmental issues, campaign and level of knowledge